Effects of race and ethnicity on hematopoietic stem cell transplant outcomes in acute myeloid leukemia: a systematic review and meta-analysis - Melo, Ana; Ahmed, Shakeel; Anzuman, Masuma; Allana, Siaana; Kilcoyne, Michelle; Nhim, Vutha; Padilla, Osvaldo; Dwivedi, Alok K.; Eiring, Anna M. (Frontiers in Oncology, 2025)
IntroductionDespite the advancements in medical facilities and treatment, acute myeloid leukemia (AML) remains a significant concern. Hematopoietic stem cell transplantation (HSCT) is the preferred treatment option for AML. However, racial and ethnic disparities have a prominent impact on HSCT outcomes due to variability in treatment availability, transplant referral, donor scarcity, socioeconomic status, and other factors.MethodsIn this systematic review and meta-analysis, we evaluated transplantation rates, relapse rates, and survival outcomes across racial and ethnic groups. A comprehensive search was conducted using PubMed, Embase, and Cochrane Library to screen relevant studies. Study quality was assessed using the MINORS scale and NIH tool, followed by an assessment of publication bias using the funnel plot and Egger’s test. A random-effects model was employed to evaluate the transplantation rate, relapse rate, and overall survival (OS). Cochran’s Q test and I2 statistic were utilized to assess the heterogeneity.ResultsA total of 781 articles were screened, and following several stages of screening according to inclusion criteria, seven full-text articles comprising nine datasets were included in the final analysis. The pooled results for transplantation and OS were not statistically significant. However, the pooled results for relapse outcome were statistically significant for both Blacks vs. Whites (risk ratio [RR] = 1.17; 95% CI: 1.04-1.32; p=0.008; I2=0.0%) and Hispanics vs. Blacks (risk ratio [RR] = 0.77; 95% CI: 0.61-0.97; p=0.027; I2==37.3%), favoring Whites and Hispanics, respectively.DiscussionMinimizing disparities in the social determinants of health across racial and ethnic groups, along with providing equity in treatment access, are needed to improve outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250644767, identifier CRD420250644767.